Training according to sensory information through visual observation in improving some biomechanical indicators of hammer throwing for Applicants - Ebadi Abid AL-Khafaji, Mohammed (International Journal of Psychosocial Rehabilitation, 2023)
Feedback with a sense of movement is the basis for the picture of correct performance in hammer throwing. This leads the  thrower  to  control  the  movements  that  occur  below  perception,  which  allows  him  to  review  other  aspects  of movement  so  that  the  feedback information  is  consistent  with  the  picture  of  motor  performance,  which  allows  the thrower to perform better in situations. Competition, and this problem the researcher wanted to find solutions to through visual monitoring of the shooter’s performance and reviewing it by the player and coach to identify the exact defect in performance and avoid it through repeated practices accompanied by this type of feedback. The research may require measuring  some  mechanical  variables  to  demonstrate  the  effectiveness  of using  feedback  through  repeated  and immediate visual review in correcting them. The research was applied to a sample of advanced Iraqi hammer throwers three  times  a  week  for  a  period  of  (6)  weeks.  Among  the  results  of  the  research  was  the  development  of  the instantaneous momentum at the moment of throwing, and the development of The resulting acceleration (vertical and tangential)  at  the  moment  the  hammer  is  fired,  the  differences  in  the  amount  of  movement  between  the  throwing position and the final throw decrease, and the final achievement improves.